2005
DOI: 10.1097/01.ede.0000152905.42113.db
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and Respiratory Emergency Department Visits

Abstract: The results of this study contribute to the evidence of an association of several correlated gaseous and particulate pollutants, including ozone, NO2, CO, PM, and organic carbon, with specific respiratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
312
6
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(357 citation statements)
references
References 26 publications
36
312
6
3
Order By: Relevance
“…Generally, the extension of the time series for an additional 4 years led to more stable risk estimates, and the observed associations are consistent with those observed in the earlier analysis (Metzger et al, 2004;Peel et al, 2005). For the two case groups examined here, we found no additional pollutant associations compared to our previous analyses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Generally, the extension of the time series for an additional 4 years led to more stable risk estimates, and the observed associations are consistent with those observed in the earlier analysis (Metzger et al, 2004;Peel et al, 2005). For the two case groups examined here, we found no additional pollutant associations compared to our previous analyses.…”
Section: Discussionsupporting
confidence: 90%
“…We previously published results for the time period 1993-2000, 2 years of which included speciated PM 2.5 data (Metzger et al, 2004;Peel et al, 2005). We now have data through 2004, tripling the period for which the speciated PM 2.5 data are available.…”
Section: Introductionmentioning
confidence: 99%
“…14 conditions. They have shown that the risk ratios for asthma visits were generally positive and strongest with a lag of 5 to 8 days (see Figure 1 in Peel et al 14 ).…”
Section: Discussionmentioning
confidence: 98%
“…Consider CO, for example. Studies have shown CO to be associated with emergency department visits and hospital admissions for asthma (Peel et al, 2005). However, ambient levels of CO are not known to have any direct effects on lung tissue (US EPA, 2000).…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 99%
“…The concern is that if this is true for asthma, could it not also be the case for heart disease, where an association is biologically plausible. The database used in Peel et al (2005) has since been extended and expanded, and Paige Tolbert of Emory University presented analyses of these data at the workshop. The investigators have been conducting an intensive spatiotemporal assessment of the roles of multiple pollutants in cardiorespiratory health outcomes, taking advantage of comprehensive air quality measurements and data on over 10 million emergency department visits for the time period 1993-2004 in Atlanta, GA.…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 99%